2011
DOI: 10.1159/000323149
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Estimation of Fetal Weight: Is Accuracy Acquired with Professional Experience?

Abstract: Objective: This study was conducted in order to determine whether experience and type of obstetrical profession improves the accuracy in the clinical estimation of fetal weight among obstetricians and midwives in the delivery room. Methods: Four groups of professionals in the delivery room clinically estimated the fetal weight in 236 parturients in active labor. Obstetric parameters such as gravidity, parity, gestational age, body mass index, amniotomy, station and cervical dilatation were recorded. Fetal weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
2
5
2
Order By: Relevance
“…Indeed, Ben-Aroya et al [21] demonstrated that seniority levels of residency did not affect the accuracy of the clinical estimation, but that residents' fatigue did. Our findings are in concordance with others' [3,8,22] , implying that there is probably no additional value for obstetrics experience to the ability to perform EFW during the active stage of labor. Since the fetal head might be engaged deep in the maternal pelvis during the active stage of labor and would be an obstacle for the measurements of the fetal BPD and HC, we used in the current study 7 different formulas for the ultrasonographic EFW.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, Ben-Aroya et al [21] demonstrated that seniority levels of residency did not affect the accuracy of the clinical estimation, but that residents' fatigue did. Our findings are in concordance with others' [3,8,22] , implying that there is probably no additional value for obstetrics experience to the ability to perform EFW during the active stage of labor. Since the fetal head might be engaged deep in the maternal pelvis during the active stage of labor and would be an obstacle for the measurements of the fetal BPD and HC, we used in the current study 7 different formulas for the ultrasonographic EFW.…”
Section: Discussionsupporting
confidence: 92%
“…5 Levin et al also demonstrated an increased error in clinical estimation of birth weight in the subgroups of birth weight <2500 grams and >4000 grams. 6 Surprisingly, in our study, a significantly higher proportion of cases of macrosomia actually were identified in obese patients than in those patients with normal BMI. It is possible that the increased thickness of the abdominal wall in cases of obesity contributes to a higher clinical EFW and, therefore, a decreased chance of missing a case of macrosomia.…”
Section: Discussioncontrasting
confidence: 67%
“…Finally, we were unable to capture individual provider level of experience; however, a recent study demonstrated that provider experience and type of obstetrical training had no significant influence on the accuracy of clinical EFW. 6 We were, however, able to capture time of year of admission and demonstrated that increasing experience during residency training throughout the academic year did not have a significant impact on the accuracy of clinical EFW.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Little difference in accuracy has been found between ultrasound and clinical measures of estimating fetal weight (e.g. fundal height) [6,7,8,9], regardless of the experience of the clinician [9]. Maternal estimates were as accurate as clinician estimates [10,11,12].…”
Section: Introductionmentioning
confidence: 99%